Some Remarks on a Group of Early Bronze Age Pottery Kept in the Istanbul Archaeological Museums - Fatih Çongur (Anadolu Araştırmaları)
This study evaluates a group of Early Bronze Age pottery kept in the İstanbul Archaeological Museums. Within the scope of this study, the material, which can be dated to the Early Bronze Age I-II, has been divided into two different ware groups according to their periods, taking into account the consistency of the paste, surface-slip colours, firing and production techniques. The material examined was divided into main form groups such as beak spouted jugs, jars, a miniature vessel and a duck vase (askos). The beak spouted jugs and pots were subsequently divided into subtypes, according to mouth, neck and body differences. Amongst the Ware 1 and Ware 2 pottery examined, beak spouted jugs with well burnished glossy surfaces, and decorated oblique/vertical reliefs dating to the EBA I, besides a very successfully fired beak spouted jug with well burnished glossy surface and grooved horizontal band and zigzag motifs dated to EBA II are most likely imitations of metal vessels. Apart from the mentioned jugs, a miniature vessel in the form of a pot with a swastika, a ‘Medallion’, a circle between waves/snakes and possibly a plant motif is also remarkable. The investigated duck vase (askos), which can be dated to the EBA III, has some similarities to examples within Phylakopi I Culture pottery. While presuming these 20 pieces of pottery originated from the Lakes District and Western Anatolia, the exact excavation sites of most of them are unknown. For this reason, comparisons shall be made between the pottery of Early Bronze Age settlements from the mentioned regions and the material examined, whereas an attempt shall be made to ascertain the probable origins of the vessels.